Serum levels of C-peptide, IGFBP-1 and IGFBP-2 and endometrial cancer risk; results from the European prospective investigation into cancer and nutrition. - Cust, A; Allen, N; Rinaldi, S; Dossus, L; Friedenreich, C; Olsen, A; Tjønneland, A; Overvad, K; Clavel-Chapelon, F; Boutron-Ruault, M; Linseisen, J; Chang-Claude, J; et al. (2007)
We conducted a case-control study nested within the European Prospective Investigation into Cancer and Nutrition, to examine the associations between prediagnostic serum concentrations of C-peptide, insulin-like growth factor binding protein (IGFBP)-1 and IGFBP-2, and endometrial cancer risk. Among pre- and post-menopausal women, who were not currently using exogenous hormones, 286 women developed incident endometrial cancer during an average 5.1 years follow-up. Using risk set sampling, 555 matched control subjects were selected. In conditional logistic regression models adjusted for matching factors only, endometrial cancer risk increased with increasing serum levels of C-peptide (relative risks (RR) for the top vs. bottom quartile = 2.13 [95% confidence interval (CI) 1.33-3.41], p(trend) = 0.001, and decreasing serum levels of IGFBP-2 (RR for the top vs. bottom quartile = 0.56 [95% CI 0.35-0.90], p(trend) = 0.03, but was not significantly associated with IGFBP-1 levels (RR for the top vs. bottom quartile = 0.76 [95% CI 0.47-1.21], p(trend) = 0.25). In BMI-adjusted models, only the C-peptide association remained marginally statistically significant (RR for the top vs. bottom quartile = 1.56 [95% CI 0.94-2.57], p(trend) = 0.05 for C-peptide; 0.84 [95% CI 0.50-1.40], p(trend) = 0.74 for IGFBP-2; and 1.08 [95% CI 0.65-1.78], p(trend) = 0.86 for IGFBP-1 levels). These associations were stronger among nonfasting women (< or =< or =6 hr since last meal; 63% of subjects) but were not evident among fasting women, although the interactions were not statistically significant. The C-peptide-risk association was substantially attenuated after adjustment for free estradiol in postmenopausal women (RR for the top vs. bottom quartile = 1.28 [95% CI 0.67-2.45], p(trend) = 0.42. Our results provide modest support to the hypothesis that hyperinsulinaemia is a risk factor for endometrial cancer.